Time-of-flight distance sensor application for counting Tetra Pak containers - Espinoza Navarrete, Dennis Omar (2024)
The present work aims to demonstrate the process by which a countingsystem is applied to a coil of Tetra Pak containers using an Arduino Uno board and a VL53L0X distance sensor, the aim is to define the distance from the coil of containers towards the sensor in order to reflect the quantity of containers remaining in real time during the production process, this quantity will be reflected on an LCD connected to the Arduino Uno. What is sought with the application of the sensor and the Arduino Uno, is to automate the counting process that was carried out manually at Arca Continental, where the operator, with the help of a flexometer, measures the distance of the coil towards a starting point, later with the help of a table the quantity was determined. of containers remaining in the warehouse to make decisions about the production process, so, with the aim of improving this procedure, an Arduino Uno card and a laser sensor are applied to measure the distance and immediately determine the number of containers in the coil in real time, this allows eliminating errors in measurement and improves safety levels for the operator.